The role of leadership in school improvement: Evaluating improvement efforts of a school in Jordan - EL TURK, ZEID (2017)
School improvement is a continuous process which is crucial to any school aiming to increase effectiveness of its outcomes. School improvement involves a wide range of intricate processes and interactions which determine the overall results. Improving, changing or removing some of these processes is vital to increasing the likelihood of achieving better results. The strategies, behaviors and decision making of school leaders can influence these processes and the degree to which they are successful. This study looks at a single case of a school in Jordan aiming to improve overall school out-comes. By looking at a single case this study aims to achieve a deeper understanding towards the hidden elements and processes involved in determining school improvement efforts.